P241 Efficacy of obinutuzumab in systemic lupus erythematosus patients with secondary non response to rituximab. (23rd April 2022) - Arnold, Jack E; Dass, Shouvik; Twigg, Sarah; Jones, Colin H; Rhodes, Benjamin; Hewins, Peter; Chakravorty, Mithun; Courtney, Phil; Ehrenstein, Michael; Yuzaiful, Md; Yusof, Md; Vital, Edward
Abstract: Background/Aims: Rituximab is a chimeric type-1 anti-CD20 monoclonal antibody approved by NHS England for refractory SLE. Secondary inefficacy with infusion reactions and anti-rituximab-antibodies occurs in 14% of re-treated patients. Obinutuzumab is a next-generation humanised type-2 anti-CD20 antibody licensed for the treatment of haematological malignancies. Methods: We collated data from nine SLE patients receiving off-label obinutuzumab for secondary non-response to rituximab with infusion reactions across six centres (Leeds, Bradford, York, UCL, Birmingham and Nottingham). Disease activity was assessed using BILAG-2004 and SLEDAI-2K and serology in local diagnostic laboratories before, and 6 months after, obinutuzumab 2x1000mg infusions 2 weeks apart alongside methylprednisolone 100mg. Results: All patients received concomitant oral immunosuppression and prednisolone. 6/9 received hydroxychloroquine. The median number of rituximab cycles before obinutuzumab therapy was 2.5. Before obinutuzumab 6/9 patients had BILAG A/B mucocutaneous, 6/9 had BILAG A/B musculoskeletal and 4/9 had BILAG A/B renal. 6 months after obinutuzumab 1/9 patients had BILAG B mucocutaneous, no patients had BILAG A/B musculoskeletal and 2/9 patients had BILAG A/B renal. Median dsDNA reduced from 118 to 83 IU/mL, C3 increased from 0.53 to 1.02g/L and C4 increased from 0.095 to 0.23g/L. Prednisolone dose was reduced in 5/9 patients; before obinutuzumab all patients received 10mg or more. After obinutuzumab, 4/9 patients received 5mg and were in Lupus Low Disease Activity State (LLDAS). Patient 5 did not respond and required further methylprednisolone and cyclophosphamide at 4 months. Patient 6 had a partial renal response but required renal transplantation, which was successful. Patient 8 responded well to obinutuzumab but died from severe COVID-19 infection (unvaccinated). After obinutuzumab 6 patients with B-cell data all achieved complete depletion including 4/4 assessed with highly sensitive assays. Conclusion: These results demonstrate obinutuzumab's efficacy in patients with secondary non-response to rituximab. These patients have severe disease with few treatment options, but previous responsiveness to B-cell depletion. Therefore, switching to another therapy in this class is mechanistically logical. Obinutuzumab appeared effective in renal and non-renal SLE as well as steroid-sparing. Immunological markers also improved. Obinutuzumab was generally well tolerated and will be further investigated for treatment-refractory lupus in the REGENCY and ALLEGORY trials. Disclosure: J.E. Arnold: None. S. Dass: Consultancies; Received consultancy fees from Roche, Abbvie, UCB & Chugai. Honoraria; Received honoraria from Roche, Abbvie, UCB & Chugai. S. Twigg: None. C.H. Jones: None. B. Rhodes: None. P. Hewins: None. M. Chakravorty: None. P. Courtney: None. M. Ehrenstein: Honoraria; Received honoraria from GSK. Grants/research support; Received funding from GSK. M. Md Yusof: None. E. Vital: Consultancies; Received consulting fees from Roche, GSK, Eli Lilly and AstraZeneca. Honoraria; Received honoraria from Roche, GSK, Eli Lilly and AstraZenec. Grants/research support; Received research support from Roche and AstraZeneca (Paid to the University of Leeds).